PENGEMBANGAN VIDEO INTERAKTIF SEBAGAI INOVASI MEDIA PEMBELAJARAN PENANGANAN CEDERA LEHER PADA REMAJA - Utomo, Seno Praditya; Paputungan, Irving Vitra; Asyhar, Alfan Nur (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
This study aims to develop an interactive video-based learning medium focused on neck injury management for adolescents aged 17–21 years, particularly in the context of football, which often involves physical collisions. The lack of understanding and skills among adolescents regarding neck injury management, as well as the limited availability of effective and engaging learning media, prompted this research. The method used is the Rapid Prototyping Model (RPM) with the ADDIE stages (Analysis, Design, Development, Implementation, and Evaluation), involving needs analysis, storyboard design, video production, trial implementation, and evaluation of effectiveness. The results showed that the interactive video successfully improved participants' understanding of neck injury management steps, with significant increases in post-test questionnaire results compared to pre-test. The strength of this video lies in its dynamic presentation, high-quality visualization, and interactive features that encourage active user engagement. This video not only provides practical education but also raises awareness among adolescents about the importance of injury prevention, making it a potentially effective and easily accessible learning medium.